2022
DOI: 10.17275/per.22.6.9.1
|View full text |Cite
|
Sign up to set email alerts
|

Teachers' attitudes and the challenges they experience concerning individualized education program (IEP): A mixed method study

Abstract: In this study, it was aimed to examine teachers' attitudes and challenges they experience concerning Individualized Education Program (IEP). Explanatory sequential design, one of the mixed methods, was used in this study. The study group of this study consists of 100 teachers working in the central districts of Van, Turkey within 2019-2020 academic year. In data collection, the scales of "Determining the Attitudes towards IEP Preparation Process", "Determining the Challenges Concerning IEP Preparation Process"… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 11 publications
1
8
0
1
Order By: Relevance
“…In the study of Kozikoglu & Albayrak (2022), among the elements that related to the level of special education teachers' knowledge of IEP includes information about the IEP implementation process, knowing the support materials that can be used to learn the IEP implementation process, knowing how to obtain support materials, knowing one's own responsibility in implementing IEP, knowing how to identify the level SEN students' current performance, knowing how to determine annual goals and knowing the intervention activities that can be implemented to achieve the IEP goals. At the same time, the results of this study contradict Kozikoglu's findings who reported that teachers do not have sufficient knowledge about the concept of IEP.…”
Section: Discussionmentioning
confidence: 99%
“…In the study of Kozikoglu & Albayrak (2022), among the elements that related to the level of special education teachers' knowledge of IEP includes information about the IEP implementation process, knowing the support materials that can be used to learn the IEP implementation process, knowing how to obtain support materials, knowing one's own responsibility in implementing IEP, knowing how to identify the level SEN students' current performance, knowing how to determine annual goals and knowing the intervention activities that can be implemented to achieve the IEP goals. At the same time, the results of this study contradict Kozikoglu's findings who reported that teachers do not have sufficient knowledge about the concept of IEP.…”
Section: Discussionmentioning
confidence: 99%
“…One of the main advantages of digital learning is the ability to build an individual learning path; there is a research on this topic [20], its purpose was to study the attitude of teachers and the problems they face in connection with the individual educational program (IEP).…”
Section: Methodsmentioning
confidence: 99%
“…However, three of the reviewed articles contradicted the findings of teacher negative attitudes towards the IEP implementation process. The three studies found that teachers showed a positive attitude towards all stages in the IEP implementation processes (Karaca et al, 2020;Kozikoğlu & Albayrak, 2022;Ruble et al, 2018).…”
Section: Teacher Attitude Challengesmentioning
confidence: 99%
“…Regarding the aspect of IEP concept, studies by Fu et al (2018) and Kozikoğlu and Albayrak (2022) showed that many teachers (f = 2; 29%) still do not understand the concept of IEP, thus affecting the IEP implementation process. The phenomenon of insufficient understanding of the IEP concept is directly linked to teachers' lack of knowledge about the support materials that are available for IEP learning and the activities that can be carried out to facilitate the IEP implementation process (Kozikoğlu & Albayrak, 2022).…”
Section: Teacher Knowledge Challengesmentioning
confidence: 99%
See 1 more Smart Citation